Human Mitochondrial DNA Polymerase Metal Dependent UV Lesion Bypassing Ability - Park, Joon; Baruch-Torres, Noe; Iwai, Shigenori; Herrmann, Geoffrey K.; Brieba, Luis G.; Yin, Y. Whitney (Frontiers in Molecular Biosciences, 2022)
Human mitochondrial DNA contains more UV-induced lesions than the nuclear DNA due to lack of mechanism to remove bulky photoproducts. Human DNA polymerase gamma (Pol γ) is the sole DNA replicase in mitochondria, which contains a polymerase (pol) and an exonuclease (exo) active site. Previous studies showed that Pol γ only displays UV lesion bypassing when its exonuclease activity is obliterated. To investigate the reaction environment on Pol γ translesion activity, we tested Pol γ DNA activity in the presence of different metal ions. While Pol γ is unable to replicate through UV lesions on DNA templates in the presence of Mg2+, it exhibits robust translesion DNA synthesis (TLS) on cyclobutane pyrimidine dimer (CPD)-containing template when Mg2+ was mixed with or completely replaced by Mn2+. Under these conditions, the efficiency of Pol γ′s TLS opposite CPD is near to that on a non-damaged template and is 800-fold higher than that of exonuclease-deficient Pol γ. Interestingly, Pol γ exhibits higher exonuclease activity in the presence of Mn2+ than with Mg2+, suggesting Mn2+-stimulated Pol γ TLS is not via suppressing its exonuclease activity. We suggest that Mn2+ ion expands Pol γ′s pol active site relative to Mg2+ so that a UV lesion can be accommodated and blocks the communication between pol and exo active sites to execute translesion DNA synthesis.